MINIMALISM IN CONTEMPORARY ARCHITECTURE AND ITS DEVELOPMENT PROSPECTS - Raximov Otabek Davlatovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores minimalism in contemporary architecture and examines its development prospects. It highlights how minimalist design principles, characterized by simplicity, functionality, and clarity, influence the aesthetics, usability, and sustainability of modern buildings. The study also discusses the future trends of minimalism, including technological integration, environmentalconsiderations, and cultural adaptation, which shape the evolution of architectural design.